PELATIHAN DAN PENDAMPINGAN PEMBUATAN SUMUR UNTUK MEMENUHI KEBUTUHAN AIR BERSIH DI DESA CIBOGO, KECAMATAN CISAUK, KABUPATEN TANGERANG - Yuda, Himmes Fitra; Amri, Muhammad Adimas; Pramadika, Havidh; Afdhal, Muhammad (Universitas Trisakti, 2025)
Cisauk district is located within the administrative area of Tangerang regency, Banten Province. The Cisauk district was originally part of the Serpong district, which experienced regional expansion. Initially, much of the land in the Cisauk district was agricultural land. However, as the population grew, its function changed to residential land, industrial trade, and services. In addition, this area in Tangerang regency is strategic as a buffer for the capital city of Jakarta. Therefore, with the increasing rate of population growth and the growth of residential areas or housing developments in the Cisauk district, the need for clean water is also directly proportional. Based on these problems, it is necessary to have training and mentoring activities in implementing clean water well-making activities, with the aim that clean water well-making activities are carried out by plans and methods that meet implementation standards and technical standards for making clean groundwater wells. It is planned to construct a borehole well at a location identified as a productive aquifer zone based on the ADMT survey results. The borehole well will be designed to reach the optimum depth to penetrate the aquifer zone, providing a sustainable, clean water supply for the community of Cibogo Village, Cisauk District.